Influence Combination Exercise William Flexion and Mckenzie Extension to Scale Painful Back Lower on Farmer - Hartono, Hartono; Darmawan, Rendi Editya; Listyowati, Devi (Basic and Applied Nursing Research Journal, 2022)
Background: Low Back Pain is one of the musculoskeletal disorders that can be experienced by those who have poor standing posture, especially farmers. Farmer risk caught low back pain caused by position work that is not ergonomically carried out continuously long, increasing with age. Method: This study used a pre-experimental research design with one group pre-post test design. Technique sampling used purposive sampling. A total of 32 respondents were involved, and the intervention was three times a week for two weeks. Scale painful be measured using the Numeric Rating Scale (NRS). Result: Results showed the scale of sore back lower before conducted intervention obtained an average of 4.06 (painful currently). After the intervention, the average scale lower back pain decreased to 2.16 (mild pain). Results analysis data using the test Wilcoxon shows the p-value = 0.000 < (0.005) value. Conclusion: There is an influence gift practice combination of William Flexion and McKenzie Extension to drop scale painful back lower on the farmer.